Gold mineralization and orogenic metamorphism in the Lena Province of Siberia as assessed from Chertovo Koryto and Sukhoi Log deposits - Yudovskaya M.A.; Distler V.V.; Prokofiev V.Y.; Akinfiev N.N. (My University, 2015)
The Chertovo Koryto gold deposit (80 t Au at 1.84 g/t) in the Lena world-class province, Siberia, is hosted in a metamorphosed sequence of the Paleoproterozoic Mikhailovsk Formation that comprises the oldest black shale strata of the Baikal-Patom region. The mineralisation is confined to the thrust zone complicated with a conjugate anticline fold, zones of shearing and dislocation. The structural position of the mineralisation is similar to that at the giant Sukhoi Log deposit in the neighbouring Mama-Bodaibo zone. In the latter, the isotope age data suggest that Khomolkho black shales, hosts to Sukhoi Log mineralisation, are of Ediacaran age and underwent prograde metamorphism during early Paleozoic. The geochemical composition of the terrigenous rocks that host Sukhoi Log, Chertovo Koryto, and a number of other deposits at the various stratigraphic levels throughout the Proterozoic sequence have much in common. They do not show elevated metal contents above the common black shale abundances, except for Au and As, which is at variance with the accepted view on diagenetic enrichment of black shales in the Lena province. The occurrence of sagenitic rutile in quartz and chlorite pseudomorphs after biotite and other petrographic observations provide evidence on a retrograde nature of the metamorphic mineral assemblages in the Mikhailovsk rocks. The sulphides are pyrrhotite and arsenopyrite with very minor pyrite at Chertovo Koryto, whereas pyrite is the predominant sulphide in the Sukhoi Log ore. Fluid inclusion data on both deposits emphasise a high-temperature nature of the mineralisation albeit revealing great contrast in the fluid composition. Sukhoi Log mineralisation was formed at mixing between low-salinity aqueous solutions and dense gaseous carbonic fluids, which facilitated effective gold scavenging and precipitation, as demonstrated by thermodynamic simulation. The precursory devolatilisation of the Mikhailovsk sediments at the prograde stage results in the paucity of gaseous carbonic fluid during retrograde metamorphism and mineralisation. The similarity in the styles and chemical parameters of mineralisation, and the predominant structural control of ore localisation within the same Precambrian regional tectonic unit support an idea that orogenic gold mineralisation in the Lena province was produced during a single early Paleozoic event.
Keywords: gold; black shales; orogenic metamorphism; orogenic fluid; Sukhoi Log; Chertovo Koryto; Докембрий::Протерозой::Палеопротерозойская; Precambrian::Proterozoic::Paleoproterozoic